Peran perbankan Dalam Pencegahan Tindak Pidana Pencucian Uang (Studi Pada Kantor Pusat PT. Bank Mestika Dharma TBK) - Ziko Hamdi; Triono Eddy; Rizkan Zulyadi (Iuris Studia: Jurnal Kajian Hukum, 2023)
The results of the study indicate that the legal rules regarding banking in relation to the prevention of money laundering in Indonesia are regulated in Law no. 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering (UU PP - ML). Bank Mestika Dharma has tried to play a role in preventing money laundering. The obstacles faced by Bank Mestika Dharma in preventing money laundering are: The internet banking and mobile banking application features do not support the obligation to fill in the source of funds and the transaction destination with a minimum nominal value of Rp. 100,000,000, it is not possible for anti-money laundering staff to monitor all daily transactions, and the difficulty of ensuring the authenticity of the Identity Card attached to account opening, as well as the bank's interest in maintaining customer convenience.